The differential association of workplace conflicts on employee well-being: The moderating role of perceived social support at work. Issue 5 (14th August 2019) - Kuriakose, Vijay; S., Sreejesh; Wilson, P.R.; MR, Anusree
Abstract : Purpose: The purpose of this study is to examine the differential association of three different workplace conflicts on employee-related outcomes, such as loneliness and well-being. Further, the study pursues to explore the perceived social support at the workplace as a conditional factor in the relation between different conflict types and employee loneliness. Design/methodology/approach: The data were collected using a self-administered survey from 554 IT employees. Structural equation modelling (SEM) was used to test the study postulations. Findings: The findings indicated that all three types of conflicts differently associate on both loneliness and well-being. Besides, it found that loneliness works as a mediator between conflict types and employee well-being. Further, perceived social support at the workplace moderates the relationship between different types of conflict, such as relationship, process, task conflicts and employee loneliness at work. Practical implications: The study provides helpful directions to HR managers by providing a clear empirical understanding of the types of conflicts and its association on employee-related outcomes. Further, the study highlights the need for developing social support in an organisation during conflict episodes, to manage the adverse association of these conflicts on employee well-being and to restore employee well-being. Originality/value: To the best of the authors' knowledge, for the first time, a study has been conducted highlighting the differential association of workplace conflict and employee outcome and indicating its intervening mechanisms and conflict management conditions.